Non-Penal efforts in countermeasures online prostitution crimes - Hasiholan Pardamean Manalu; Maya Shafira; Ahmad Irzal Fardiansyah; Firganefi Firganefi; Aisyah Muda Cemerlang (Goodwood Publishing, 2022)
Purpose: This study analyzes the laws and regulations that apply to legal phenomena and online prostitution. Research Methodology: This study uses a normative juridical method and analyzes the laws and regulations that apply to legal phenomena and online prostitution. Results: The factors that cause online prostitution are as follows:1. internal factors, such as family and friendships, and 2. External factors such as avoiding tracking officers and economic factors to obtain large amounts of money quickly. Preventive efforts can be made through educational facilities, means of economic equality and employment in the informal sector, increasing social and cultural awareness starting from the neighborhood of Neighborhood Groups (RT), and supervising boarding houses or apartments/flats so as not to be misused as a place of prostitution. The repressive efforts that can be carried out are through the provision of legal sanctions based on prevailing laws and regulations, online prostitutes, users of commercial sex workers, prostitutes, and pimps. The purpose of the criminal sanctions is to make deterrence so that no other people will carry out online prostitution & so that these former prisoners can be well received in society.